2021
DOI: 10.1002/joc.7156
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the origins of moisture over Vietnam: The role of moisture sources and atmospheric drivers on seasonal hydroclimatic conditions

Abstract: A Lagrangian approach is used to identify the seasonal climatological moisture sources of the seven climate subregions of Vietnam during 1980–2017. Using the outputs from the FLEXPART model, three main oceanic moisture sources, located in the Arabian Sea, Bay of Bengal, and China Seas, and three terrestrial moisture sources, located in the Indian Peninsula, East Asia, and South Asia, are identified. The most important moisture source during the rainy season (May–October) is the Bay of Bengal, followed by the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 79 publications
3
8
0
Order By: Relevance
“…The water vapor channel over the Indian Ocean agrees with the findings of Stojanovic et al (2021), who identified this as the dominant moisture source for precipitation over Vietnam. In comparison with their study, we found an additional moisture source over the South China Sea and a parallel water vapor channel over the Bay of Bengal for the larger occurrence number of extreme precipitation during 2003-2015.…”
Section: Change In Water Vapor Transportsupporting
confidence: 87%
See 1 more Smart Citation
“…The water vapor channel over the Indian Ocean agrees with the findings of Stojanovic et al (2021), who identified this as the dominant moisture source for precipitation over Vietnam. In comparison with their study, we found an additional moisture source over the South China Sea and a parallel water vapor channel over the Bay of Bengal for the larger occurrence number of extreme precipitation during 2003-2015.…”
Section: Change In Water Vapor Transportsupporting
confidence: 87%
“…In contrast, water vapor for precipitation during the summer monsoon is largely provided by moisture transport from the South China Sea. Moreover, the identification of moisture sources has received an increasing attention in the analysis of both extreme precipitation and a changing hydrological cycle due to climate change (Gimeno et al, 2013;Stojanovic et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, Rodwell and Hoskins (1995) estimated that 60%-80% of moisture transported by the SLLJ is from the southern hemisphere subtropical high. Stojanovic et al (2021) showed that the Bay of Bengal is the most important moisture source for part of South-East Asia during the dry season (May-October) and the South China Sea is the most important moisture source during the dry season (November-April), consistent with the flux-weighted density maps in Figure 12.…”
Section: 𝑿𝑿𝑿𝑿supporting
confidence: 79%
“…For this reason, the SPEI (Vicente-Serrano et al, 2010) was utilised, which includes the role of temperature through AED in the assessment of drought. Besides, the SPEI has been widely used, demonstrating its usefulness for the most realistic representation of dry conditions that affect a given region (Hernandez and Uddameri, 2014;Wang et al, 2015;Ghebrezgabher et al, 2016;Delbiso et al, 2017;Stojanovic et al, 2018;Drumond et al, 2019;Tefera et al, 2019;Sorí et al, 2020;Stojanovic et al, 2021b).…”
Section: Standardised Precipitation Evapotranspiration Indexmentioning
confidence: 99%